Winnie The Pooh: A Very Grand Thing - Milne, A A (Egmont Children's Books Ltd, 1999)
It is a Blusterous Day.Pooh and Piglet are visiting Owl to wish him a very Happy Thursday,when suddenly Owl's house is blown down and they are stuck inside.
Keywords: Juvenile literature-Fiction